Single-nucleus CUT&RUN elucidates the function of intrinsic and genomics-driven epigenetic heterogeneity in head and neck cancer progression - Womersley, Howard J.; Muliaditan, Daniel; DasGupta, Ramanuj; Cheow, Lih Feng (Genome Research, 2025)
Interrogating regulatory epigenetic alterations during tumor progression at the resolution of single cells has remained an understudied area of research. Here we developed a highly sensitive single-nucleus CUT&RUN (snCUT&RUN) assay to profile histone modifications in isogenic primary, metastatic, and cisplatin-resistant head and neck squamous cell carcinoma (HNSCC) patient–derived tumor cell lines. We find that the epigenome can be involved in diverse modes to contribute toward HNSCC progression. First, we demonstrate that gene expression changes during HNSCC progression can be comodulated by alterations in both copy number and chromatin activity, driving epigenetic rewiring of cell states. Furthermore, intratumor epigenetic heterogeneity (ITeH) may predispose subclonal populations within the primary tumor to adapt to selective pressures and foster the acquisition of malignant characteristics. In conclusion, snCUT&RUN serves as a valuable addition to the existing toolkit of single-cell epigenomic assays and can be used to dissect the functionality of the epigenome during cancer progression.
10.1101/gr.279105.124